2019
DOI: 10.1002/ese3.514
|View full text |Cite
|
Sign up to set email alerts
|

A parametric study to simulate the non‐Newtonian turbulent flow in spiral tubes

Abstract: One of the ways to improve heat transfer efficiency is to use a spiral structure for tubes instead of conventional direct tubes. Compared to the direct tubes, spiral tubes have a more compact surface and have higher heat transfer and friction coefficients. When the fluid flows through the spiral tubes, it influences by the centrifugal force which this centrifugal force creates a secondary flow in the fluid, and as a result, this secondary flow increases the axial flow velocity near the outer wall of the tube. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…First, velocity distribution changes considerably as fluid flows near the junction of the cone and the tube or the outlet . Second, friction head loss is caused by the viscosity of the fluid because the inner surface of the Marsh funnel is not perfectly slippery . Lastly, the changes in momentum are due to the mixing of viscous fluid molecules .…”
Section: Mathematical Models For Flow Fieldmentioning
confidence: 99%
“…First, velocity distribution changes considerably as fluid flows near the junction of the cone and the tube or the outlet . Second, friction head loss is caused by the viscosity of the fluid because the inner surface of the Marsh funnel is not perfectly slippery . Lastly, the changes in momentum are due to the mixing of viscous fluid molecules .…”
Section: Mathematical Models For Flow Fieldmentioning
confidence: 99%
“…Since the governing Equations (6) and (7) are highly coupled and nonlinear, to the best of our information, it is difficult to find their analytical solutions based on the current theory. Some numerical methods, and the calculation software have been applied as an effective tool to simulate the flow of non-Newtonian fluids [31][32][33]. In this section, the numerical solutions of governing Equations (6) and 7are obtained by an effective finite difference method.…”
Section: The Numerical Techniquementioning
confidence: 99%
“…Geothermal energy is heat from the inner part of the earth that is present in rocks and water in cracks and pores within the rock of the earth's crust. The temperature normally increases with depth, although not in a constant manner [1][2][3][4]. The benefits of geothermal energy include reduced pollution and avoidance of change in ecosystems' reliability and renewability.…”
Section: Introductionmentioning
confidence: 99%
“…Heberle et al [2] studied an ORC with geothermal sources. A combination of heat and power generation for the geothermal sources was proposed at a temperature below 450 K. The results showed that the best choice of working fluid is R227a.…”
Section: Introductionmentioning
confidence: 99%